Estudos de validação da técnica de detectores de estado sólido de traços nucleares para determinação de radônio-222 no ar e monitoramento em centros de educação infantil de Poços de Caldas-MG - Dias, Danila Carrijo Da Silva (2017)
Radon gas (222Rn) is a natural radionuclide and its inhalation represents on average more than 50% of the annual dose of radiation to which men are subjected on average. The World Health Organization and the International Atomic Energy Agency recommend the control of human exposure to this gas, as it diffuses from rocks and soils, entering living environments and concentrating indoors. It is recommended that radon surveys follow quality control procedures in order to obtain reliable data. This work proposed validation studies of the Solid State Nuclear Track Detectors (SSNTD) technique for the determination of indoor 222Rn concentrations. Additionally, this technique was applied in the monitoring of early child education centers located in Poços de Caldas-MG. The method was based on the use of CR-39 passive detectors and an automated nuclear track analysis system. The validation studies began with participation in an international intercomparison exercise of passive radon detectors. The experimental data produced in the exercise were applied to performance tests that evaluated the method’s accuracy, precision, linearity, work range, uncertainty and the detection limit. An independent experiment evaluated robustness. The performance results complied to the established acceptance criteria and suggested opportunities for method improvement. The determination of radon concentrations in the early child education centers involved the installation of 377 detectors in 45 locations, for approximately one year. The resulting overall mean concentration of 82 Bq.m-3 is comparable to the Brazilian average value released by UNSCEAR.